Curriculum Alignment and Learning Outcomes in Primary Education - Yuni Misrahayu; Marastika Wicaksono Aji Bawono; Tri Nathalia Palupi; Ahmad Faqihudin; Miftahuddin Miftahuddin (Mandalika Institute, 2026)
This study examines the relationship between curriculum alignment and learning outcomes in primary education through a qualitative library research approach. The study aims to analyze how coherence among curriculum objectives, instructional content, teaching and learning activities, and assessment practices contributes to the improvement of student learning outcomes. The data were derived from selected scholarly literature discussing constructive alignment, outcome-based curriculum design, curriculum mapping, instructional coherence, assessment alignment, curriculum progression, and holistic learning outcomes. The analysis was conducted through systematic reading, thematic classification, conceptual extraction, and critical synthesis of the selected sources. The findings indicate that curriculum alignment functions as a systemic and pedagogical framework that connects intended learning outcomes with classroom instruction and assessment. Aligned curricula support clearer competency targets, coherent instructional sequences, valid assessment practices, and continuity of learning across grade levels and educational stages. The study also shows that learning outcomes in primary education should not be limited to academic achievement, but should include conceptual understanding, engagement, socio-emotional development, and readiness for lifelong learning. The study concludes that curriculum alignment is a fundamental prerequisite for improving the quality of primary education because it enables teachers, schools, curriculum developers, and policymakers to ensure that curriculum intentions are translated into meaningful and measurable learning experiences.